The interplay between monetary and fiscal policies in the EU - Afonso, António (2020)
We study the interactions between monetary and fiscal policies in the EU countries, for the period 1995-2019. Our results show notably that: i) the inflation rate has a relevant impact over the central banks’ decision making; ii) the cyclically adjusted primary balance reacts positively to increases in the level of government debt; iii) monetary policy reaction functions do not seem to take into consideration the cyclically adjusted primary balance; iv) fiscal policy, via the cyclically adjusted primary balance, seem to be affected by the short-term interest rate in a negative way. The global economic and financial crisis impacted negatively both the short-term nominal interest rates and the cyclically adjusted primary balance, however with a higher degree in the euro area.